2005
DOI: 10.1172/jci24459
|View full text |Cite
|
Sign up to set email alerts
|

NO/redox disequilibrium in the failing heart and cardiovascular system

Abstract: There is growing evidence that the altered production and/or spatiotemporal distribution of reactive oxygen and nitrogen species creates oxidative and/or nitrosative stresses in the failing heart and vascular tree, which contribute to the abnormal cardiac and vascular phenotypes that characterize the failing cardiovascular system. These derangements at the integrated system level can be interpreted at the cellular and molecular levels in terms of adverse effects on signaling elements in the heart, vasculature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
155
0
7

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(164 citation statements)
references
References 102 publications
2
155
0
7
Order By: Relevance
“…regulation of the channels is also through NO release through NOS3 activation. 63) Although there is evidence of direct s-nitrosylation of cardiac I Ca,L channels, 64,65) our results indicate differential mechanisms of the NO regulation through NOS3 between the I Ca,L channel and the I Ks channel, suggesting a compartmentalized regulation of I Ca,L and I Ks by NO. However, the mechanism for the compartmentalization of this NO regulation of cardiac ion channels has not been clarified.…”
Section: Non-genomic Regulation Of Cardiac Ion Channels By Sex Steroimentioning
confidence: 60%
“…regulation of the channels is also through NO release through NOS3 activation. 63) Although there is evidence of direct s-nitrosylation of cardiac I Ca,L channels, 64,65) our results indicate differential mechanisms of the NO regulation through NOS3 between the I Ca,L channel and the I Ks channel, suggesting a compartmentalized regulation of I Ca,L and I Ks by NO. However, the mechanism for the compartmentalization of this NO regulation of cardiac ion channels has not been clarified.…”
Section: Non-genomic Regulation Of Cardiac Ion Channels By Sex Steroimentioning
confidence: 60%
“…The authors suggested that it may be that L-NMAE is transported into the cell using either diffusion or a transport system other than cationic amino acid transporter used by L-NMA [28,29]. In addition, NO is a part of the complex redox system that are known to be heavily involved in multiple cardiovascular signal transduction systems, which regulate contractility, blood flow, and heart rate [30][31][32]. Nevertheless, both inhibitors demonstrated similar results in this study and their effect on heart rate is minimal.…”
Section: Discussionmentioning
confidence: 99%
“…NO mediates a large number of physiological and pathophysiological effects via its cellular effector cGMP and cGMPindependent mechanisms (9). In dystrophin-deficient skeletal muscle, neuronal NO synthase (nNOS, one of the enzymes responsible for NO production) is displaced away from its normal subsarcolemmal location to the cytoplasm, where its mislocalization and decreased activity level are thought to contribute to muscle pathology (10)(11)(12)(13).…”
mentioning
confidence: 99%